(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The principal target of this empirical study is to deliver an investigation to analyse the effect of Foreign Direct Investment and International remittances on economic growth of the nations situated in Central Asia for the years 2009 – 2019. The panel data for the study was extracted from the World Bank Statistics. Gross Domestic product was chosen as dependent variable, while Foreign Direct Investment, International Remittances, Trade openness, Population growth indicators were selected as independent variables. The existing research analysis showed that the influence of FDI on economic progress is positive, while, mixed results have been found for the impact of International Remittances on economic growth. The regression analysis of econometric model was obtained from the following employed models: Ordinary Least Squares (OLS), Random Effects, Fixed Effects, GLS model. In order to avoid from the issues of multicollinearity, heteroscedasticity, cross-sectional dependence, some important diagnostic tests were conducted. The empirical findings of the study reveals that the FDI acquires statistically significant and positive relationship with economic growth, whilst, international remittances, population growth, trade have a statistically insignificant and negative correlation with economic development. It concludes that Foreign Direct Investment plays a key role in boosting the economic development of the selected countries.